Immunization of Cattle with Tick Salivary Gland Extracts - Ali Nikpay; Sedigheh Nabian (Tehran University of Medical Sciences, 2016)
Background: Rhipicephalus (Boophilus) annulatus tick is one of the most important ectoparasite of cattle. Recently, several laboratories in the world have been concentrated on immunizing cattle against tick using various types of tissue extracts of ticks. The aim of this study was to evaluate the effect of immunization of cattle with tick salivary gland extract on biological parameters of ticks and humoral immune responses of cattle. Methods: Fourteen more dominant protein bands identified as immunogenic by Western-blot analysis were eluted from polyacrylamide gel. Test and control groups were injected three times with eluted proteins and sterile PBS (pH= 7.2) respectively with equivalent amount of adjuvant. After four weeks a tick challenge was performed. Finally, biological parameters of collected engorged female ticks were recorded and humoral immune responses to immunization measured by ELISA. Results: The results indicated immunization of cattle resulted in reduction in mean tick counts, attachment, engorgement weights, feeding index, egg mass weight, hatchability and fertility index (respectively 63.1%, 62.6%, 30.2%, 36.4%, 40%, 78.7% and 13.3%) and increased duration of feeding, pre-oviposition and incubation period of eggs (respectively 8.6%, 45 and 31.34%). All changes were statistically significant (P< 0.05). Results showed an increase in antibody production of test group from the first week after immunization. The antibody level was boosted following tick infestation. Conclusion: This investigation indicates that immunization of cattle with these antigens could induce a protective immune response against Rh. (B.) annulatus tick that would be expected to provide a safe non-chemical means of tick control.